Voxel-based morphometry in amyotrophic lateral sclerosis - I. S. Bakulin; R. N. Konovalov; M. V. Krotenkova; N. A. Suponeva; M. N. Zakharova (Вестник рентгенологии и радиологии)
Objective: to investigate changes in grey matter volume in patients with classical amyotrophic lateral sclerosis (ALS) and lower motor neuron syndrome (LMNS) with voxel-based morphometry (VBM).Material and methods. 30 patients with classical ALS, 22 patients with LMNS and 23 age and gender matched healthy controls were enrolled in this study. All participants underwent a T1MPR (multiplanar reconstruction) magnetic resonance imaging with post-processing included spatial normalization, segmentation and smoothing. VBM was used to investigate changes in grey matter volume across the groups.Results. There was a significant decrease in grey matter volume of middle part of left pre- and postcentral gyri, middle part of right precentral gyrus, right and left occipital lobes in patients with classical ALS compared to healthy subjects. There was no difference in grey matter volume between patients with LMNS and healthy controls. Patients with classical ALS showed a significant decrease in grey matter volume of middle part of left preand postcentral gyri, upper part of left precentral gyrus, middle and upper parts of right precentral gyrus, right and left occipital lobes compared to patients with LMNS. There was no significant correlation between grey matter volume and clinical findings in patients with ALS and LMNS.Conclusion. VBM reveals a decrease in grey matter volume of motor and nonmotor brain regions in patients with classical ALS, but not in patients with LMNS.